Teachers' and Students' Perceptions Towards the Implementation of Independent Curriculum in English Learning - Zebua, Meniati; Zebua, Agustin Ceria; Waruwu, Puspa Triyani; Bate'e, Juni For Enjelina; Waruwu, Friska Putri; Julvin Oryentika Waruwu (Indonesian Journal Publisher, 2025)
This study aims to investigate teachers’ and students’ perceptions of the implementation of the independent curriculum in English language learning. Conducted across six different schools (two elementary schools, two junior high schools, and two senior high schools), the research use the qualitative approach using a descriptive phenomenological design. The data were collected through interviews and questionnaires. The findings reveal that teachers perceive the independent curriculum as providing greater flexibility and creativity in teaching, enabling them to implement student-centered approaches and innovative methods such as using visual media, learning modules and technology. Teachers also value the variety of assessments, including diagnostic, formative, and summative evaluations. However, challenges such as administrative burdens and gaps in students' abilities remain significant. From the students' perspective, the curriculum is seen as engaging and interactive, with project-based tasks enhancing motivation and skill development. Nevertheless, students face difficulties in mastering vocabulary and grammar and building self-confidence, often exacerbated by unequal access to learning resources. This study concludes that the Independent Curriculum has significant potential to enhance English language learning by fostering active student engagement and teacher innovation. To maximize its effectiveness, recommendations include providing adequate resources, reducing administrative burdens, and enhancing teacher training to address implementation challenges.